The migrated intrauterine contraceptive device presented as a vesical stone - Chun-Cheng Lin; Meng-Hung Shih; Chih-Wei Tsao (Journal of Medical Sciences, 2023)
Intrauterine devices (IUDs) are one of the most popular reversible contraception methods. However, if an event related to them is unanticipated, or if they are not located when missing, it can be dangerous. We present a case of chronic lower abdomen pain and recurrent urinary tract infection ongoing for 1.5 years. Despite the patient undergoing laparoscopic uterine myomectomy, her symptoms had not improved. The patient visited a genitourinary clinic for lower urinary tract symptoms and accepted cystoscopy and electrohydraulic lithotomy. Incidentally, a part of an IUD was found in the calculus. This case highlights the need for careful diagnosis and for locating missing IUDs to avoid serious complications.